Clinical and Epidemiological Implications of 24‐Hour Ambulatory Blood Pressure Monitoring for the Diagnosis of Hypertension in Kenyan Adults: A Population‐Based Study. Issue 12 (December 2016) - Etyang, Anthony O.; Warne, Ben; Kapesa, Sailoki; Munge, Kenneth; Bauni, Evasius; Cruickshank, J. Kennedy; Smeeth, Liam; Scott, J. Anthony G.
Abstract : Background: The clinical and epidemiological implications of using ambulatory blood pressure monitoring (ABPM) for the diagnosis of hypertension have not been studied at a population level in sub‐Saharan Africa. We examined the impact of ABPM use among Kenyan adults. Methods and Results: We performed a nested case–control study of diagnostic accuracy. We selected an age‐stratified random sample of 1248 adults from the list of residents of the Kilifi Health and Demographic Surveillance System in Kenya. All participants underwent a screening blood pressure (BP) measurement. All those with screening BP ≥140/90 mm Hg and a random subset of those with screening BP <140/90 mm Hg were invited to undergo ABPM. Based on the 2 tests, participants were categorized as sustained hypertensive, masked hypertensive, "white coat" hypertensive, or normotensive. Analyses were weighted by the probability of undergoing ABPM. Screening BP ≥140/90 mm Hg was present in 359 of 986 participants, translating to a crude population prevalence of 23.1% (95% CI 16.5–31.5%). Age standardized prevalence of screening BP ≥140/90 mm Hg was 26.5% (95% CI 19.3–35.6%). On ABPM, 186 of 415 participants were confirmed to be hypertensive, with crude prevalence of 15.6% (95% CI 9.4–23.1%) and age‐standardized prevalence of 17.1% (95% CI 11.0–24.4%). Age‐standardized prevalence of masked and white coat hypertension were 7.6% (95% CI 2.8–13.7%) and 3.8% (95% CI 1.7–6.1%), respectively. The sensitivity and specificity of screening BP measurements were 80% (95% CI 73–86%) and 84% (95% CI 79–88%), respectively. BP indices and validity measures showed strong age‐related trends. Conclusions: Screening BP measurement significantly overestimated hypertension prevalence while failing to identify ≈50% of true hypertension diagnosed by ABPM. Our findings suggest significant clinical and epidemiological benefits of ABPM use for diagnosing hypertension in Kenyan adults.